Porovnání screeningových a konfirmačních metod v diagnostice syfilis - Kuklová, Ivana; Dražďáková, Marcela; Zákoucká, Hana (Iga MZ ČR, 2007)
During 2004 and 2006 comparison of sensitivity and specifity of reference screening methods TPPA, TPHA and VDRL, imunochromatographic rapid tests/Determine Syphilis TP/ and EIA total will be carried out. In positive or uncertain cases reference confirmatory reactions 19S IgM, SPHA, FTA-ABS IgG a IgM, Elisa IgM, westernblot total and TPIt will be conducted and compared. Retrospective analysis of clinical findings in the patients with early and late syphilis examined at the STD center of the Dermatovenerology clinic in Prague will be carried out. The data concerning the serologic findings in prostitutes will serve as source documents for the European Commision -EUROPAP study / European network of HIV/STD prevention in prostitution/.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Serologic Tests; radiologie, nukleární medicína a zobrazovací metody; sérologická diagnostika syfilis; plošný screening; ELISA; Mass Screening; Enzyme-Linked Immunosorbent Assay; retrospektivní studie; Syphilis Serodiagnosis; sérologické testy; dermatovenerologie; infekční lékařství; Retrospective Studies